Proceso de ASC - ESTUDIO DE MATERIALES CERAMICOS PARA APLICACIONES MEDICAS FASE 2 (2019)
The rapid population growth in recent years has significantly increased the demand for implants, which have traditionally been developed from metallic materials. However, due to the inherent disadvantages of these materials, ceramic implants have been developed, creating a market worth approximately 253 billion dollars annually. Ceramic materials possess several key characteristics that make them suitable for implants, such as biocompatibility, osteoconductivity, easy adhesion, porosity, neutral pH, and excellent mechanical properties. In the Colombian context, there is a noticeable lack of contributions in the field of implants, particularly ceramic ones. This gap presents an opportunity to conduct research that can bring new ideas, propose innovative formulations to tackle new challenges, improve existing implants, and much more, all with the goal of making significant advances in this important global issue. For these reasons, after conducting a technology assesment in the SCOPUS database and engaging in several discussions with experts on the topic, it was observed that Portland cement, commonly used in construction, is an alternative that has not been widely studied.. Thus, it was decided to investigate whether this material is indeed suitable for medical applications. This required studying all the processes needed for Portland cement to meet the mechanical and biological characteristics that would make it a biocompatible material. In essence, the goal of this project is to determine whether Portland cement can be used as a ceramic implant, evaluate its advantages and disadvantages compared to other materials used so far, and explore how to enhance its performance.